A comparison methodology for measured and predicted displacement fields in modal analysis. (21st July 2017) - Sebastian, C.M.; López-Alba, E.; Patterson, E.A.
Abstract: Recent advances in experimental mechanics have enabled full-field measurements of deformation fields and - particularly in the field of solid mechanics - methodologies have been proposed for utilizing these fields in the validation of computational models. However, the comparison of modal shapes and the path from the undeformed shape to the deformed shape at the extreme of a vibration cycle is not straightforward. Therefore a new method to compare vibration data from experiment to simulations is presented which uses full-field experimental data from the entire cycle of vibration. Here, the first three modes of vibration of an aerospace panel were compared, covering a frequency range of 14–59 Hz and maximum out-of-plane displacements of 2 mm. Two different comparison methodologies are considered; the first is the use of confidence bands, previously explored for quasi-static loading, the second is the use of a concordance correlation coefficient, which provides quantifiable information about the validity of the simulation. In addition, three different simulation conditions were considered, representing a systematic refinement of the model. It was found that meaningful conclusions can be drawn about the simulation by comparing individual components of deformation from the image decomposition process, such as the relative phase and magnitude. It was ultimately found that the best performing model did not entirely fall within the confidence bounds for all conditions, but returned a concordance correlation coefficient of nearly 70% for all three modes.